THE EFFECT OF RISK PERCEPTIONS AND BENEFITS PERCEPTIONS ON CONSUMER BEHAVIOR ONLINE SHOPPING WITH THE IMPACT OF THE COVID-19 PANDEMIC AS A MODERATION VARIABLE - Siti Chamidah; Dwi Warni Wahyuningsih; Sri Hartono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Pandemic Covid 19 has resulted in uncertainty in various business sectors, and is a new challenge for the business sector to create new strategies by optimizing digital marketing with online marketing. To formulate an effective and optimal online marketing strategy, online marketers must be able to understand the factors that influence consumer behaviour. Covid 19 pandemic too bring about shifts in consumer behaviour and change online consumer perceptions good about risk perception as well as perception benefit purchase online. This research aims to find out whether impact of the covid pandemic 19 plays a role in moderating the effect of perceived risk and perceived benefits on online shopping consumer behaviour on society Ponorogo. In this study there are four hypotheses to be tested. This research uses an explanatory quantitative approach using primary data obtained through a questionnaire on line. Questionnaires were taken using a non-probability sampling technique, namely purposive sampling, with the number of samples used by 100 respondents. In testing, this study uses Regression analysis with moderation (Moderation Regression Analysis) with the help of SPSS software. The results of the study concluded that perceived risk and perceived benefits had a significant effect on online consumer behaviour, and the impact of the Covid 19 pandemic proved to have no significant effect on the relationship between perceived risk and perceived benefits on consumer behaviour. Keywords: Perceived risk, perceived benefits, online consumer behaviour, the impact of the covid pandemic.